USING SCHOOLOGY APPLICATION TO IMPROVE THE DESCRIPTIVE TEXT WRITING SKILL OF THE TENTH GRADERS OF SMA MUHAMMADIYAH 1 MUNTILAN IN THE SCHOOL YEAR OF 2018/2019 - durrotun nafisah (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2019)
AbstractIn teaching English, there are four language skills. They are listening, speaking, reading, and writing. Writing is one of the important skills in teaching English. However, the tenth graders of SMA Muhammadiyah 1 Muntilan in the school year of 2018/2019 still got difficulties in writing, especially in writing descriptive text. It was caused by the students’ low motivation in learning writing and the monotonous media that are used by the teacher. There are two objectives of this research. First, to know whether or not there is any improvement of the descriptive text writing learning motivation taught by using Schoology Application. Second, to know how great is the improvement of the students’ descriptive text writing skill taught by using Schoology Application.The writer conducted a classroom action research. The subject of this research was X IPS 2 of SMA Muhammadiyah 1 Muntilan in the school year of 2018/2019. The writer used test and non-test (observation sheet, questionnaire, and documentation) to collect the data. The writer used qualitative and quantitative data as the technique of analyzing data.The observation percentage in Pre-Cycle is 49.30% and it becomes 79.86% in Cycle II. The total improvement is 30.56%. In Pre-Cycle test, the average score of writing descriptive text is 62.75. After the writer used Schoology Application as media, the students average score in Cycle I is 66.78 while in Cycle II is 78.06. Overall the total improvement from Pre-Cycle test to Cycle II test is 15.31 points.Keywords: Descriptive Text, Schoology Application, Writing Skill.